SARS-CoV-2 Antigen Rapid Test in The Emergency Department; a Diagnostic Accuracy Study - Saeed Safari; Faezeh Golpour; Mohammad Mehdi Forouzanfar; Behrooz Hahsemi; Shahram Ebrahimi (طب اورژانس ایران, 2023)
Title: Evaluation of diagnostic value of SARS-CoV-2 rapid diagnostic test in patients with Covid-19